Agents of Resurrection in 4Q521, 4QPseudo-Ezekiel, and the Saying Source Q - Wold, Benjamin (My University, 2010)
This article brings recent developments in the analysis of 4Q521 and Q into conversation with a previously undiscussed document related to resurrection: 4QPseudo-Ezekiel
Judaism in Antiquity Seminar
PUBLISHED
Durham University
Keywords: Theology and Religion; Saying Source Q; 4Q521; Messianic Apocalypse